Driving and Inhibiting Factors to Tourist Interest in Visiting Lamalera - Antonio E. L. Nyoko; Ronald P. C. Fanggidae; Paulus L. Blikololong (Penerbit Goodwood, 2023)
Purpose: This study aims to identify and examine the drivers that increase tourist interest in visiting Lamalera village as well as the inhibiting factors that discourage tourist interest in visiting Lamalera village. Methodology: The data collection procedures used in this study include observation and interview of local and foreign visitors who came to see the whaling tradition (Kotekelema) in the fishing village of Lamalera, Wulandoni sub-district. Result: This study concluded that the drivers of visitors' interest in Lamalera are the allure of whaling culture, the availability of transportation to tourist sites, and the amenities such as houses of worship and health care facilities. The inhibiting factors to the interest of visiting tourists in Lamalera are the unavailability of additional tourist attractions in addition to whaling culture in this place, the accessibility issue concerns very long travel routes, bad road conditions, poor network conditions, and access to insufficient information regarding Lamalera cultural tourist objects, the absence of prayer rooms, restaurants, public restrooms, souvenir stores, diving equipment, and the hospitality component of tourist services, which is deemed inadequate.